2019
DOI: 10.1038/s41588-019-0497-5
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of common schizophrenia risk variants

Abstract: The mechanisms by which common risk variants of small effect interact to contribute to complex genetic disorders remain unclear. Here, we apply a genetic approach, using isogenic human induced pluripotent stem cells (hiPSCs), to evaluate the effects of schizophrenia-associated common variants predicted to function as brain expression quantitative trait loci (SZ-eQTLs). By integrating CRISPR-mediated gene editing, activation and repression technologies to study one putative SZ-eQTL (FURIN rs4702) and four top-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
198
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(217 citation statements)
references
References 80 publications
13
198
0
Order By: Relevance
“…For example, genetic polymorphisms exist in the ACE2 gene [2], which encodes the cellular receptor for SARS-CoV-2; allelic variants of the ACE2 may influence the protein's binding with the virus [3] and subsequent invasion of the cell. In addition, polymorphisms of cellular proteases-believed to facilitate the entry of SARS-CoV-2 into the cell, along with furin [4] and TMPRSS2 [5]-have been shown to exist [6,7]. Indeed, a recent preprint suggests that TMPRSS2 variants and resulting expression may influence COVID-19 severity [8].…”
Section: Genomics Of Susceptibility and Resistancementioning
confidence: 99%
“…For example, genetic polymorphisms exist in the ACE2 gene [2], which encodes the cellular receptor for SARS-CoV-2; allelic variants of the ACE2 may influence the protein's binding with the virus [3] and subsequent invasion of the cell. In addition, polymorphisms of cellular proteases-believed to facilitate the entry of SARS-CoV-2 into the cell, along with furin [4] and TMPRSS2 [5]-have been shown to exist [6,7]. Indeed, a recent preprint suggests that TMPRSS2 variants and resulting expression may influence COVID-19 severity [8].…”
Section: Genomics Of Susceptibility and Resistancementioning
confidence: 99%
“…As combination of ATP6V1A KD and Aβ treatment led to a greater amount of molecular expression change than individual factor perturbation, we explored potential synergistic effects between the two factors 59 . We first modeled the additive effect of differential expression in the individually modulated samples computationally.…”
Section: Neuronal Knockdown Of Vha68-1 a Fly Ortholog Of Atp6v1a Womentioning
confidence: 99%
“…Assays of downstream consequences of variation also confirm biological convergence across association loci. A four-gene-target CRISPRi/a assay revealed that schizophrenia risk genes act synergistically via shared influence on synaptic activity, and concurrent alteration of expression of all four genes results in a cellular transcriptome more accurately reflective of postmortem schizophrenia brain tissue (99). For both rare and common variants, identifying common regulators among risk genes provides information which can refine predictions of disease-related cell types based on their expression of such TFs, RBPs, or epigenomic marks.…”
Section: The Utility Of Mpras For Parsing Linked Variationmentioning
confidence: 99%